Building a culture of workplace wellness: Perspectives from Philippine organizations - Hechanova, Ma. Regina (Archīum Ateneo, 2018)
This study explored approaches to building a culture of wellness in the workplace from a developing country perspective. Focus group discussions with HR practitioners and health professionals in the Philippines were conducted. Deductive thematic analysis was used to organize the data. Results showed that organizations use a variety of strategies in building workplace wellness, which could be classified using the CREATE framework – Communicate, Role model, Engage employees, Align systems, structures and policies, Train, Evaluate and reinforce. The identified strategies and CREATE framework can be utilized as a guide for organizations planning to implement workplace wellness initiatives in a holistic manner.